2000
DOI: 10.1054/bjoc.1999.1051
|View full text |Cite
|
Sign up to set email alerts
|

Hevin is down-regulated in many cancers and is a negative regulator of cell growth and proliferation

Abstract: We have cloned a human Hevin cDNA from omental adipose tissue of different patients by reverse transcription polymerase chain reaction and shown a sequence variation due to a possible polymorphism at amino acid position 161 (E/G). Hevin protein expressed in vitro showed molecular weights of approximately 75 kDa and 150 kDa, suggesting that Hevin may form a homodimer in vitro. Using Northern blots and a human expressed sequence tAg database analysis, Hevin was shown to be widely expressed in human normal or non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 27 publications
7
55
0
2
Order By: Relevance
“…In the growth and proliferation of various tumor cells, SPARCL1 often presents decreased expression as a negative regulative factor, which may be closely related to the increase of the cell proliferation activity and the cell cycle progression (Claeskens et al, 2000). Particularly, growing evidence shows that SPARCL1 often presents a reduced or absent expression pattern in a variety of human tumor tissues (Bendik et al, 1998;Nelson et al, 1998;Isler et al, 2004;Esposito et al, 2007;Zaravinos et al, 2011;Hurley et al, 2012;Li et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the growth and proliferation of various tumor cells, SPARCL1 often presents decreased expression as a negative regulative factor, which may be closely related to the increase of the cell proliferation activity and the cell cycle progression (Claeskens et al, 2000). Particularly, growing evidence shows that SPARCL1 often presents a reduced or absent expression pattern in a variety of human tumor tissues (Bendik et al, 1998;Nelson et al, 1998;Isler et al, 2004;Esposito et al, 2007;Zaravinos et al, 2011;Hurley et al, 2012;Li et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The high endothelial venules are special round post-capillary venules as opposed to the flat endothelial cells found in regular venules, and enable high levels of lymphocytes in the blood to enter the lymphatic system. SPARCL1 participates in many physiological functions such as cell proliferation and muscle differentiation, and can promote lymphocyte transportation through adjusting the endothelial cell adhesion function (Girard and Springer, 1996;Claeskens et al, 2000). SPARCL1 is expressed in many tissues and organs such as heart, lung, brain, bone, muscle, colon and lymphatic gland, but it has a lower expression in pancreas, spleen, thyroid gland and placental tissue and even SPARCL1 is not expressed in liver, kidney and peripheral blood leucocytes (Girard and Springer, 1995;Hambrock et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no specific functional data are available, Mok et al (1994) identified DOC1 (downregulated in ovarian cancer) using a DNA-fingerprinting approach to find genes differentially expressed between ovarian cancer cells and normal ovarian epithelial cells. SPARC-like 1 (SPARCL1, MAST9, hevin, SC-1) is a member of the SPARC family (Claeskens et al, 2001). This gene was originally shown to be downregulated in human non-small cell lung cancer and subsequent reports indicated that downregulation of SPARCL1 also occurs in prostate and colon carcinomas (Bendik et al, 1998;Isler et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Sparcl1 markedly inhibited prostate epithelial bud elongation; however, comparable expression of proliferation markers in Sparcl1-treated prostate organ cultures suggests that Sparcl1 does not regulate proliferation in the prostate. Because Sparcl1's role in proliferation is varied, we further defined SPARCL1-mediated regulation of prostatic epithelial cell growth (10,18,19). We examined cellular proliferation and death in SPARCL1-treated prostate cells and demonstrated that SPARCL1 did not restrict the growth of multiple prostate cancer cell lines (Fig.…”
Section: Sparcl1 Expression Is Suppressed During Adult Prostate Regenmentioning
confidence: 99%